1975
DOI: 10.1111/j.1365-2362.1975.tb02311.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Pattern of Lipids in Normal and Dystrophic Human Muscle

Abstract: The fatty acid distribution of the main lipid fractions: triglycerides (TG), phosphatidylcholine (PCh) , phosphatidylethanolamine (PE) , and sphingomyelin (Sph) of muscle from 6 patients with progressive muscular dystrophy (p.m.d.), Duchenne, 8 to 12 years old was estimated and compared with normal controls of different age. In view of the results of several authors about varied fatty acid distribution in immature muscle a third group comprising samples of neonatal muscle was studied. 1 . The fatty acid patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Additionally, membrane vesicles possess the ability to transport lipid droplets in human astrocytes and rat adipocytes (Muller et al, 2009;Falchi et al, 2013). Cell membrane dysfunction could lead to fatty acid metabolism disturbances (Kunze et al, 1975). Our results suggest that bdmew may play a key role in fatty acid metabolism.…”
Section: Discussionmentioning
confidence: 79%
“…Additionally, membrane vesicles possess the ability to transport lipid droplets in human astrocytes and rat adipocytes (Muller et al, 2009;Falchi et al, 2013). Cell membrane dysfunction could lead to fatty acid metabolism disturbances (Kunze et al, 1975). Our results suggest that bdmew may play a key role in fatty acid metabolism.…”
Section: Discussionmentioning
confidence: 79%
“…This applies particularly to choline phosphoglyceride, ethanolamine phosphoglyceride and sphingomyelin. Takagi et al (1968) and Kunze et al (1975) reported an increase in the fatty acid 18:1 and a decrease in 18:2 in phosphatidylcholine in dystrophic muscle. Kunze et al (1975) also analysed phosphatidylethanolamine and sphingomyelin, but their profiles even for normal muscle were unusual.…”
Section: Discussionmentioning
confidence: 96%
“…Takagi et al (1968) and Kunze et al (1975) reported an increase in the fatty acid 18:1 and a decrease in 18:2 in phosphatidylcholine in dystrophic muscle. Kunze et al (1975) also analysed phosphatidylethanolamine and sphingomyelin, but their profiles even for normal muscle were unusual. A similar criticism has been levelled at their data for erythrocytes (Plishker and Appel, 1980) and suggests that there is some problem in their methodology.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Compared with those in their wild-type counterparts on the same diet, skeletal muscle phospholipid (PL) in mdx mice exhibit increased oleic acid (18 : 1) and linoleic acid (18 : 2) abundances and reduced DHA (22 : 6) abundance ( 3 ) . Results from similar assessments of fatty acid (FA) composition in the muscle of human subjects with DMD are unclear due to a lack of dietary control in these studies ( 4 – 6 ) as well as issues related to age matching and sample handling ( 5 ) . In DMD and the mdx mouse, the skeletal muscle sarcolemma is destabilised as a result of a mutation in the dystrophin gene ( 2 ) .…”
mentioning
confidence: 99%